2005
DOI: 10.1007/s10530-004-8978-5
|View full text |Cite
|
Sign up to set email alerts
|

Biological characteristics of an invasive south African species

Abstract: Senecio inaequidens, a south African species that has recently invaded parts of Europe, especially human disturbed habitats, was examined under laboratory and glasshouse conditions to assess the germination of achenes, soil seed banks, growth of seedlings and its breeding system. These observations allowed identification of ecological characteristics that may contribute to the invasiveness of the species. Achenes derived from three populations of S. inaequidens were germinated over a wide temperature range (fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
35
0
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(40 citation statements)
references
References 40 publications
3
35
0
2
Order By: Relevance
“…Sexual reproduction is mainly allogamous and is initiated in late spring (May–June), approximately two months after massive germination, and continues through late autumn (November–December). Ex situ germination tests have indicated that germination is absent at temperatures below 2°C [37]. Entomophilous pollination with generalist pollinators is most common.…”
Section: Methodsmentioning
confidence: 99%
“…Sexual reproduction is mainly allogamous and is initiated in late spring (May–June), approximately two months after massive germination, and continues through late autumn (November–December). Ex situ germination tests have indicated that germination is absent at temperatures below 2°C [37]. Entomophilous pollination with generalist pollinators is most common.…”
Section: Methodsmentioning
confidence: 99%
“…inaequidens extends to 1 m tall with numerous stems bearing yellow capitulae. Individuals can produce up to 1,500 capitulae over a flowering period, each capitulum bearing roughly 100 achenes (hereafter referred to as "seeds") (Lopez-Garcia and Maillet 2005). Sexual reproduction initiates in late spring (May-June), approximately 2 months after germination, and continues through late autumn (November-December).…”
Section: Study Species and Invasion Historymentioning
confidence: 99%
“…Sexual reproduction initiates in late spring (May-June), approximately 2 months after germination, and continues through late autumn (November-December). The species is considered self-incompatible, but some individuals were observed exhibiting partial self-fertility in France (Lopez-Garcia and Maillet 2005). Entomophilous pollination with generalist pollinators is most common.…”
Section: Study Species and Invasion Historymentioning
confidence: 99%
“…This perennial herb presents a self-incompatible reproductive system and is pollinated by insects; the effective fruit production is high, with 75% viable achenes, which are well dispersed by wind and animals (Lopez-Garcia and Maillet 2005). This species was introduced in the south of France (Mazamet) in 1936 and then observed in Gare d'Austerlitz (a Parisian railway station) in 1990 (Henry and Maurin 1999).…”
Section: What About Exotic and Invasive Species?mentioning
confidence: 99%